Evaluation of fat accumulation and adipokine production during the long-term adipogenic differentiation of porcine intramuscular preadipocytes and study of the influence of immunobiotics - Tada, Asuka (2020)
The degree of fat accumulation and adipokine production are two major indicators of obesity that are correlated with increased adipose tissue mass and chronic inflammatory responses. Adipocytes have been considered effector cells for the inflammatory responses due to their capacity to express Toll-like receptors (TLRs). In this study, we evaluated the degree of fat accumulation and adipokine production in porcine intramuscular preadipocyte (PIP) cells maintained for in vitro differentiation over a long period without or with stimulation of either TNF-α or TLR2-, TLR3-, or TLR4-ligands. The cytosolic fat accumulation was measured by liquid chromatography and the expression of adipokines (CCL2, IL-6, IL-8 and IL-10) were quantified by RT-qPCR and ELISA at several time points (0 to 20 days) of PIP cells differentiation. Long-term adipogenic differentiation (LTAD) induced a progressive fat accumulation in the adipocytes over time. Activation of TLR3 and TLR4 resulted in an increased rate of fat accumulation into the adipocytes over the LTAD. The production of CCL2, IL-8 and IL-6 were significantly increased in unstimulated adipocytes during the LTAD, while IL-10 expression remained stable over the studied period. An increasing trend of adiponectin and leptin production was also observed during the LTAD. On the other hand, the stimulation of adipocytes with TLRs agonists or TNF-α resulted in an increasing trend of CCL2, IL-6 and IL-8 production while IL-10 remained stable in all four treatments during the LTAD. We also examined the influences of several immunoregulatory probiotic strains (immunobiotics) on the modulation of the fat accumulation and adipokine production using supernatants of immunobiotic-treated intestinal immune cells and the LTAD of PIP cells. Immunobiotics have shown a strain-specific ability to modulate the fat accumulation and adipokine production, and differentiation of adipocytes. Here, we expanded the utility and potential application of our in vitro PIP cells model by evaluating an LTAD period (20 days) in order to elucidate further insights of chronic inflammatory pathobiology of adipocytes associated with obesity as well as to explore the prospects of immunomodulatory intervention for obesity such as immunobiotics.